2018
DOI: 10.1089/scd.2017.0291
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dissolved Oxygen Levels on Human Mesenchymal Stem Cell Culture Success, Regulatory Compliance, and Therapeutic Potential

Abstract: Most cells in the human body, including human mesenchymal stem cells (hMSCs), have evolved to survive and function in a low physiological oxygen (O) environment. Investigators have become increasingly aware of the effects of O levels on hMSC biology and culture and are mimicking the natural niche of these cells in vitro to improve cell culture yields. This presents many challenges in relation to hMSC identity and function and in the maintenance of a controlled O environment for cell culture. The aim of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 177 publications
(173 reference statements)
0
19
0
Order By: Relevance
“…From the 41 retained studies, information regarding the freezing solution composition, the freezing protocol, the duration of storage, the concentration of cells at freezing, the passage number at freezing as well as the thawing method was extracted and tabulated. Next, studies were grouped in tables according to the “hMSC checklist” proposed in [24]. Cell surface marker expression, differentiation potential, proliferation and growth, attachment and migration potential, genomic stability and paracrine function were examined.…”
Section: Methodsmentioning
confidence: 99%
“…From the 41 retained studies, information regarding the freezing solution composition, the freezing protocol, the duration of storage, the concentration of cells at freezing, the passage number at freezing as well as the thawing method was extracted and tabulated. Next, studies were grouped in tables according to the “hMSC checklist” proposed in [24]. Cell surface marker expression, differentiation potential, proliferation and growth, attachment and migration potential, genomic stability and paracrine function were examined.…”
Section: Methodsmentioning
confidence: 99%
“…Their therapeutic potential has been proved in diverse tissue engineering applications such as wound healing [ 27 ], bone regeneration [ 28 ], small diameter vascular graft fabrication [ [29] , [30] , [31] ], and cardiac repair [ 32 ]. Moreover, previous studies have shown that physiologically low (2%) oxygen preserves the stemness and paracrine effects of hMSCs [ [33] , [34] , [35] ]. Therefore, in this study, hMSCs were selected as model cells to further examine their cellular response toward PD based surface coatings under the physiological hypoxic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to cancer cells, it has been found that hMSC proliferation, migratory capacity, and function can be enhanced in hypoxic conditions. It is reported that low O 2 percentages (3%) can stimulate a greater yield of hMSCs when cells are cultured in low oxygen for a number of days [23], and can significantly enhance proliferative ability by approximately 10 population doublings compared to ambient O 2 levels (20%) [24]. Therefore, from the wider literature, it can be seen that both cancer cells and hMSCs can thrive in hypoxic conditions in vitro, where other mammalian cells would perish.…”
Section: Discussionmentioning
confidence: 99%